2013
DOI: 10.1007/s11571-013-9247-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of EEG abnormalities in the early stage of Parkinson’s disease

Abstract: The objective of the present study was to investigate brain activity abnormalities in the early stage of Parkinson's disease (PD). To achieve this goal, eyes-closed resting state electroencephalography (EEG) signals were recorded from 15 early-stage PD patients and 15 agematched healthy controls. The AR Burg method and the wavelet packet entropy (WPE) method were used to characterize EEG signals in different frequency bands between the groups, respectively. In the case of the AR Burg method, an increase of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
100
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 49 publications
12
100
0
1
Order By: Relevance
“…Decreased β and γ frequency energy and increased θ frequency energy was observed in the PD-D and AD patients, indicating these patients underwent a slowing of brain oscillatory activity, which is consistent with previous reports [8][9][10][11][12][13][14][15][16]. Slow EEG activity implies that neural activity in the information processing of the brain has become less complex and thus simpler dynamics exist in brains cognitively impaired by dementia.…”
Section: Discussionsupporting
confidence: 90%
“…Decreased β and γ frequency energy and increased θ frequency energy was observed in the PD-D and AD patients, indicating these patients underwent a slowing of brain oscillatory activity, which is consistent with previous reports [8][9][10][11][12][13][14][15][16]. Slow EEG activity implies that neural activity in the information processing of the brain has become less complex and thus simpler dynamics exist in brains cognitively impaired by dementia.…”
Section: Discussionsupporting
confidence: 90%
“…However, several spectral studies with EEG/MEG (Olde Dubbelink et al 2013;Stoffers et al 2007;Neufeld et al 1994;Han et al 2013) have observed an increase in theta or delta powers for PD patients compared to controls. Our results of relative power in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We referred {c 1 , c 2 , c 3 , …, c q , r 2 } as to AR parameters. The power spectral density (PSD) for y(n) was Han et al 2013). …”
Section: Autoregressive Burg Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with classical spectrum estimation methods (e.g. FFT), AR Burg method can reduce the spectral losses and give better frequency resolution (Akin and Kiymik 2000;Han et al 2013). Nowadays, quantitative studies have shown that AD causes EEG signals to slow down.…”
Section: Introductionmentioning
confidence: 99%